Trade, economic and welfare impacts of the CARICOM-Canada free trade agreement - Jeetendra Khadan; Roger Hosein (Inter-American Development Bank (IDB), 2016)
This paper estimates the trade, revenue, and welfare effects of the proposed Caribbean Community (CARICOM)-Canada free trade agreement (FTA) on CARICOM countries using a partial equilibrium model. The welfare analysis also takes into account the Economic Partnership Agreement, which was signed in 2008 by the CARIFORUM (CARICOM and the Dominican Republic) countries and the European Union. The revealed comparative advantage index, trade complementarity index, and transition probability matrices are used to examine the dynamics of comparative advantage for CARICOM countries' exports to Canada. The results obtained from the partial equilibrium model indicate adverse revenue and welfare effects for CARICOM member states. The results from various trade indices used do not provide evidence to suggest that an FTA between CARICOM countries and Canada can improve trade outcomes.
Keywords: F13; F14; F17; 330; CARICOM-Canada FTA; partial equilibrium model; welfare effects; comparative advantage